Ocena sposobu zywienia, stanu odzywienia, wydatków energetycznych zwiazanych z obciazeniem treningowym oraz bilansu energetycznego mlodziezy uprawiajacej pilke nozna - Bajerska-Jarzebowska, J.; Jeszka, J.; Kostrzewa-Tarnowska, A. (Medycyna sportowa, 2003)
Introduction. The aim of this study was to estimate the compositions of diet and nutritional status of young soccer players as well as to estimate the influence of the training load on the amount of their total energy expenditure (TEE). Materials and methods. Fifteen young male soccer players (SP) from Lódz, at the age of 15 participated in this study. Dietary intake and nutrients were assessed by 24 dietary recall method. The nutritional status was evaluated basing on anthropometrical indices: (height, weight). Analysis of the body composition-percentage of adipose tissue (FM) and lean body mass (FFM) was performed by electric impedance technique (BIA). TEE were assessed by the non-invasive method of 24 h heart rate monitoring. Each subject was individually "calibrated" under standardized conditions in order to establish the relationship between HR and VO2. Results. Average weight at the height of 170 cm was 58 kg what allows to put this group between 25 and 50 percentile of growths charts. Body composition of the young players was 18,2% ± 3,1 and 81,8% ± 3,2 for FM and FFM respectively. The football players diets were not properly balanced for only several nutrients (Ca, P, wit. C). However, the percentage of the energy in the diets from the macronutrients was far from recommended for sportsmen. Carbohydrates and proteins supplied too low energy e.g. 48% and 11% respectively, while fats far too much - 41%. TEE was 3239 kcal ± 432 and the main part of TEE (39%) was due to the daylong training (4,5 h). Energy cost of training equal to 4,8kcal/kg.m.c.* h ± 0,9 proved that training load was relatively height. The energy content of football players diets (3711,0 kcal ± 530) covered with surplus (ca. 470 kcal) their TEE. Introduction. The investigations indicated the necessity to monitor of nutritional status and habits of the young football players as the source of important data for preparing well balanced diets.